Defining the fitness of HIV-1 isolates with dual/mixed co-receptor usage. Issue 1 (December 2015) - Nankya, Immaculate; Tebit, Denis; Abraha, Awet; Kyeyune, Fred; Gibson, Richard; Jegede, Oyebisi; Nickel, Gabrielle; Arts, Eric
Abstract Background CCR5-using (r5) HIV-1 predominates during asymptomatic disease followed by occasional emergence of CXCR4-using (x4) or dual tropic (r5x4) virus. We examined the contribution of the x4 and r5 components to replicative fitness of HIV-1 isolates. Methods Dual tropic r5x4 viruses were predicted from average HIV-1 env sequences of two primary subtype C HIV-1 isolates (C19 and C27) and from two patient plasma samples (B12 and B19). Chimeric Env viruses with an NL4-3 backbone were constructed from the B12 and B19 env sequences. To determine replicative fitness, these primary and chimeric dual tropic HIV-1 were then competed against HIV-1 reference isolates in U87.CD4 cells expressing CXCR4 or CCR5 or in PBMCs ± entry inhibitors. Contribution of the x4 and r5 clones within the quasispecies of these chimeric or primary HIV-1 isolates were then compared to the frequency of x4, r5, and dual tropic clones within the quasispecies as predicted by phenotypic assays, clonal sequencing, and 454 deep sequencing. Results In the primary HIV-1 isolates (C19 and C27), subtype C dual tropic clones dominated over x4 clones while pure r5 clones were absent. In two subtype B chimeric viruses (B12 and B19), r5 clones were >100-fold more abundant than x4 or r5/x4 clones. The dual tropic C19 and C27 HIV-1 isolates outcompeted r5 primary HIV-1 isolates, B2 and C3 in PBMCs. When AMD3100 was added or when only U87.CD4.CCR5 cells were used, the B2 and C3 reference viruses now out-competed the r5 component of the dual tropic C19 and C27. In contrast, the same replicative fitness was observed with dualtropic B12 and B19 HIV-1 isolates relative to x4 HIV-1 A8 and E6 or the r5 B2 and C3 viruses, even when the r5 or x4 component was inhibited by maraviroc (or AMD3100) or in U87.CD4.CXCR4 (or CCR5) cells. Conclusions In the dual tropic HIV-1 isolates, the x4 replicative fitness is higher than r5 clones but the x4 or x4/r5 clones are typically at low frequency in the intrapatient virus population. Ex vivo HIV propagation promotes outgrowth of the x4 clones and provides an over-estimate of x4 dominance in replicative fitness within dual tropic viruses.